Utilização das teleconsultorias em saúde bucal no núcleo Telessaúde Bahia: um estudo acerca da incorporação dessa tecnologia no processo de trabalho das equipes de saúde bucal - Lima, Adeilda Ananias de (2023)
This study aims to analyze the use of the teleconsultation service in oral health, by oral health teams, at the Núcleo Telessaúde Bahia. This is an analytical-descriptive research that presents a methodological approach of a qualitative nature. It is based on theoretical discussions and exploration of the contexto through semi-structured interviews carried out in four cities in Bahia, involving fourteen professionals from oral health teams. These professionals were distributed into two representative groups: Group I (Professionals from oral health teams who used the Telessaúde Bahia Platform) and Group II (Professionals from oral health teams who did not use the Telessaúde Bahia Platform). Data analysis was carried out using Thematic Content Analysis. The findings indicate that workers in oral health teams consider the offer of teleconsultation as a permanent education tool, capable of providing support in decision-making in daily actions.